FROM PRESUMPTIONS OF FACT TO PRESUMPTIONS OF CAUSATION: REFLECTIONS ON THE PERILS OF JUDGE-MADE RULES IN QUEBEC MEDICAL MALPRACTICE LAW - Kouri, Robert (Revue de droit de l'Université de Sherbrooke, 2001)
Several Quebec judgments rendered in cases involving medical malpractice contain pronouncements alluding to circumstances under which causation may be presumed. While the Common law is amenable to the elaboration of principles derived from a process of inductive reasoning, the Civil Code relies on deductive reasoning in order to establish causation by presumption of fact. The writer queries whether dicta apparently originating from certain Common law decisions should be received in Quebec Civil law.